Modern Approaches to Obesity Treatment – literature review - Mateusz Romaniuk; Maria Wachowska; Wojciech Sowiński; Paweł Maciej Rycąbel; Marta Szymura; Marek Jarosław Molenda; Oliwia Woszczyńska; Agnieszka Ewelina Wojciechowska; Michał krawczyk; Mateusz Paniak (Quality in Sport)
Abstract